Analysis of Fulfillment of the Objectives for Sustainable Development in Romania - Razvan-Aurelian Munteanu (Ovidius University Annals: Economic Sciences Series, 2023)
The paper represents an analysis of the fulfillment of the indicators assumed in SDG no. 1 "No poverty", from Romania. The analysis aims at ranking all the member states of the European Union, with an emphasis on Romania, according to three indicators, respectively: real GDP/capita, persons at risk of poverty or social, severe housing deprivation rate. The correlation of the ranks of the three indicators demonstrates that, although there are states with a high standard of living, registering high values of the macroeconomic aggregate GDP/capita, however, they also face social problems, especially regarding persons at risk of poverty or social exclusion.